New results on anti-synchronization of switched neural networks with time-varying delays and lag signals. (September 2016) - Cao, Yuting; Wen, Shiping; Chen, Michael Z.Q.; Huang, Tingwen; Zeng, Zhigang
Abstract: This paper investigates the problem of global exponential anti-synchronization of a class of switched neural networks with time-varying delays and lag signals. Considering the packed circuits, the controller is dependent on the output of the system as the inner states are very hard to measure. Therefore, it is necessary to investigate the controller based on the output of the neuron cell. Through theoretical analysis, it is obvious that the obtained ones improve and generalize the results derived in the previous literature. To illustrate the effectiveness, a simulation example with applications in image encryptions is also presented in the paper.